2013
DOI: 10.1530/rep-12-0399
|View full text |Cite
|
Sign up to set email alerts
|

Molecular morphology and function of bull spermatozoa linked to histones and associated with fertility

Abstract: Sub-par fertility in bulls is influenced by alterations in sperm chromatin, and it might not be solved with increased sperm concentration in artificial insemination. Appropriate histone retention during sperm chromatin condensation plays critical roles in male fertility. The objective of this study was to determine failures of sperm chromatin condensation associated with abnormal persistence or accessibility of histones by aniline blue (ANBL) test, expression levels, and cellular localizations of one variant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 74 publications
2
42
0
Order By: Relevance
“…Errors within spermatogenesis relating to the condensation of the DNA as well as maintenance of epigenetic marks could plausibly explain the differences in embryonic gene expression. Indeed, less DNA condensation, protamine exchange, and higher DNA damage have been observed in spermatozoa of lower fertility bulls in comparison to higher fertility bulls [73, 74]. Therefore, future studies should focus on better identification of spermatogenesis errors as well as on epigenetic marks that have an effect on the embryonic transcriptome and if these errors are associated with fertility status and developmental outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Errors within spermatogenesis relating to the condensation of the DNA as well as maintenance of epigenetic marks could plausibly explain the differences in embryonic gene expression. Indeed, less DNA condensation, protamine exchange, and higher DNA damage have been observed in spermatozoa of lower fertility bulls in comparison to higher fertility bulls [73, 74]. Therefore, future studies should focus on better identification of spermatogenesis errors as well as on epigenetic marks that have an effect on the embryonic transcriptome and if these errors are associated with fertility status and developmental outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Sperm nuclear structure is also crucial important for fertility. Experiments have demonstrated that bull sperm contain a repertoire of histones fertility (De Oliveira et al, 2013) and that amounts of Protamine 1 (PRM1) in sperm are directly correlated with bull reproductive performance (Dogan et al, 2015). These studies indicate that different amounts of histones, as well as the ratios between protamines and histones, determine sperm viability and thus bull fertility.…”
Section: Sperm Proteins and Fertilitymentioning
confidence: 99%
“…However, this information becomes available only after animals are mature and have been selected for commercial use in the AI industry. Moreover, criteria such as sperm motility and morphology have limited associations with the actual fertility of sires, particularly in groups of animals that have been extensively selected by the AI industry (Killian et al, 1993;Moura, 2005;Moura et al, 2006;De Oliveira et al, 2013;Dogan et al, 2015;Kaya and Memili, 2016). Significant differences in fertility exist among bulls with "normal" semen parameters and bulls with non-compensable sperm defects may never achieve adequate fecundity (De Oliveira et al, 2013;Dogan et al, 2015;Kaya and Memili, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Another histone, H4, is important for proper chromatin remodeling during spermatogenesis and is necessary for the zygote to inherit the correct chromosomal structure. These examples show that paternal histones play important roles in early embryonic development and can be analyzed to evaluate male fertility (3).…”
Section: Molecular Determinants Of Bull Fertilitymentioning
confidence: 99%
“…Reliable fertility data are essential for research as well as production. For example, the fertility prediction for individual bulls can be obtained using the Probit.F90 software and is expressed as the percent deviation of its conception rate from the average conception rate of all bulls (3,4). Significant fertility differences exist among bulls producing spermatozoa with apparently normal motility, morphology, and numbers.…”
Section: Introductionmentioning
confidence: 99%